LONG-TERM EFFECT OF WARMING-INDUCED PERMAFROST THAWING ON TUNDRA VEGETATION—THE EVIDENCE FROM THE CHUKCHI PENINSULA (RUSSIAN NORTHEAST) - Alexey Maslakov; Mikhail Grishchenko; Alina Grigoryan; Dmitry Zamolodchikov (Zbornik Radova: Geografski institut "Jovan Cvijić")
Tundra is one of the most sensitive environments of the world in relation to climate changes, since its ecosystems exist close to the limits of plant community tolerance. Besides, tundra vegetation in most of Arctic regions resides on permafrost, which is thermally unstable media. Thus, vegetation and frozen soils are extremely vulnerable to external impacts and are balancing in fragile thermodynamic equilibrium. Thermal and moisture regime shifting lead to changing of thermophysical properties of vegetation cover and thus, the thermal balance of underlying permafrost. In this study we present the results of 2001–2024 in-situ monitoring of vegetation cover and permafrost conditions in remote region of the Chukchi Peninsula, Russian Northeast. The study combines the yearly data on active layer thickness and vegetation cover from two sites of Circumpolar Active Layer Monitoring (CALM) program located within the key site of Eastern Chukotka Coastal Plains (ECCP). The study reveals long-term trajectories of climate, permafrost, and vegetation cover characteristics. Although common biological productivity was growing and active layer was thickening, the particular plant species respond to these changes differently. On sloping plots, the increasing of active layer thickness (ALT) led to correspondent lowering of the permafrost table, drainage of thawing ice and thus, soil drying, which caused the decrease in moss and sedge covers. Meanwhile, within flat poorly-drained surfaces the permafrost thawing contributes to soil moisture with correspondent sedge expansion. Thermokarst-affected terrain triggers the growth of tundra vegetation bioproductivity and serves as a shelter for plants from Arctic winds and facilitates higher snow accumulation.